THE UTILIZATION OF THE INSTAGRAM LIVE FEATURE IN LEARNING DURING PANDEMIC TIMES TO IMPROVE STUDENTS' SPEAKING ABILITIES - Riri Narasati (Universitas Galuh, 2022)
The main reason for this research is the boredom of online learning that many students have to deal with. Moreover, this condition has existed since more than a year ago. This situation alone makes the researcher, who also acts as a teacher, upgrade the online learning process with the help of social media, the Instagram Live feature. The researcher hopes that the online learning process can be more fun and enjoyable by using the Instagram Life feature, which will later improve the students' speaking ability. This research investigates using the Descriptive Statistical method, which uses class control and the class experiment. The data shown are Pre-Test and Post Test data which are then processed using Wilcoxon. This way, in the final of the research, it can be concluded that the use of Instagram live can improve Speaking skills because there is a significant score difference between before and after using Instagram live as a learning process.